Assessing the performance of recycled asphalt mixtures using rejuvenators - Sameer Ahmed Mufti,; Fazli Karim,; Qaiser Iqbal,; Sher Afzal Khan,; Hanif Ullah,; Shahid Iqbal,; Noman Khan,; Diyar Khan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
After serving their intended purpose, traditional asphalt pavements are destroyed and dumped across the neighboring fields in Pakistan, affecting the natural environment. Only 15% of the old asphalt material has been recycled on the Motorway (M-2) near Shekhupura. Thus, the current study was intended to increase the amount of recycled asphalt, utilizing waste engine oil (WEO), waste cooking oil (WCO), and waste brown grease (WBG) as rejuvenators. Therefore, the asphalt mixture containing 50% recycled materials, rejuvenated with 5%, 10%, 15%, 20%, and 25% WEO, WCO, and WBG, respectively, were investigated. The asphalt samples for Marshall Stability, indirect tensile strength, and rut resistance were prepared and tested as per ASTM D1559, ASTM D979, and ASTMD8360, respectively. The results showed that WEO, WCO, and WBG of 15% and 20%, respectively, are best for equating the properties of recycled binder to those of neat binder, except for ductility characteristics. The results also demonstrated that, in comparison to the traditional asphalt mixture, asphalt mixes with 50% recycled materials performed significantly better in terms of Marshall stability at 15% utilization of WEO, WCO, and WBG, respectively. Additionally, it is established that recycled asphalt mixture, at WEO of 15%, displayed equivalent rut resistance to virgin asphalt mixture. The results of this study will help recycle old asphalt materials for practical engineering purposes, lowering the dependence on natural resources and benefiting the environment.